HIGH-RESOLUTION RECORDS OF LOCATION AND STRATIGRAPHIC PROVENANCE FROM THE RARE EARTH ELEMENT COMPOSITION OF FOSSIL BONES - Trueman C.N.; Behrensmeyer A.K.; Potts R.; Tuross N. (My University, 2006)
Bone apatite acts as a natural, timed sampling device, scavenging trace elements from local pore waters over timescales of ca. 1-50 ka. The rare earth element (REE) and U/Th composition of fossil bones reflects associated pore water compositions during the period of recrystallisation. The REE composition of fossil bones is controlled by partitioning of REE between pore waters and particle surfaces, and the REE composition of fossil bones reflects the REE composition of pore waters which vary spatially and temporally. Light REE are preferentially sorped onto particle surfaces, thus the high La/Yb values seen in many bones from coastal marine and aeolian environments are best explained by release of REE from light REE-enriched particles to local pore waters and subsequent immobilisation in recrystallising bones. The REE compositions of bones recovered from pedogenically altered diatomite sediments of the Olorgesailie Formation of southern Kenya vary over spatial scales of less than 10 m. Location accounts for 48% of the observed variation in bone chemistry and bones recovered from eight discrete excavations within the same time-equivalent stratigraphic layer can be assigned to their excavation location with >70% accuracy based on a discriminant analysis of REE, U, and Th composition. Despite this within-layer variation, bones recovered from different stratigraphic horizons within the Olorgesailie Formation can also be distinguished on the basis of their trace element composition. Bones recovered from four stratigraphic horizons spanning ca. 0.5 million years were assigned to their correct stratigraphic layer with >90% accuracy. Where sedimentological conditions are favourable, the trace element composition of fossil bone may be used to test stratigraphic provenance and burial location in excavated bone with a temporal resolution of <10 ka and a spatial resolution of <10 m. The trace element composition of fossil bone may also be used to investigate the accumulation history of vertebrate assemblages and to reconstruct pore water variability across land surfaces. © 2006 Elsevier Inc. All rights reserved.